2008
DOI: 10.1002/jbm.a.31904
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of low‐crystallinity hydroxyapatite foam based on the setting reaction of α‐tricalcium phosphate foam

Abstract: Low-crystallinity hydroxyapatite (HAP) foam is an ideal material for bone substitutes and scaffolds for bone tissue regeneration, because its interconnected pores provide the space for cell growth and tissue penetration, and its composition induces excellent tissue response and good osteoconductivity. In this study, the feasibility of low-crystallinity HAP foam fabrication was evaluated based on the phase transformation reaction or the so-called dissolution-reprecipitation reaction of alpha-tricalcium phosphat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 23 publications
1
26
0
Order By: Relevance
“…In this study, NH3 solution was preferred to other strong basic media to avoid any extra ionic substitution in apatite structure. The incorporation of NH 4 + ion (ionic radius: 1.45 Å) in the apatite structure (ionic radius of Ca + : 1.00 Å) seems to be difficult due to its large ionic radius 8) . Therefore, a calcium-deficient apatite free of cationic substitution can be obtained as shown by the Ca/P ratio measured in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, NH3 solution was preferred to other strong basic media to avoid any extra ionic substitution in apatite structure. The incorporation of NH 4 + ion (ionic radius: 1.45 Å) in the apatite structure (ionic radius of Ca + : 1.00 Å) seems to be difficult due to its large ionic radius 8) . Therefore, a calcium-deficient apatite free of cationic substitution can be obtained as shown by the Ca/P ratio measured in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Our reserach group has been reported that low crystalline HAp block and HAp foam were prepared using gypsum (CaSO 4•2H2O) block and alpha tricalcium phosphate (α-TCP) foam as the precursor 3,4) . For the formation of HAp block, gypsum block was immersed in (NH4)2HPO4 and treated at 60°C, 80°C and 100°C for a prescribed period.…”
Section: Introductionmentioning
confidence: 99%
“…The artificial bones usually require post-fabrication sintering process to increase their mechanical properties, which causes contraction in size and often decreases biodegradability, as well as shape adjustment during surgery [110][111][112][113]. Therefore, there is a need for novel artificial bones that have better shape compatibility to deformities, appropriate mechanical strength without the post-fabrication sintering, and biodegradability.…”
Section: Scaffolds For Bone Tissue Engineeringmentioning
confidence: 99%
“…One of the key advantages of the BC method is that coating can be performed at room temperature. It has been reported that apatite sintered at lower temperature shows better osteoconductivity 12) . Therefore, BC may allow fabrication of apatite-coated Ti implants with higher osteoconductivity.…”
Section: Introductionmentioning
confidence: 99%